Corporate Tax Avoidance and Shareholders Returns: Moderating Effects of Monitoring - Ikponmwosa Michael Igbinovia; Chizoba Marcella Ekwueme (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2018)
The study tests the moderating effect of monitoring on the corporate tax avoidance- shareholders’ returns nexus in quoted Nigerian firms. Using an ex-post facto design, annual financial data were collected from 54 non-financial firms from various sectors of the Nigerian Stock Exchange (NSE). Analyses were carried out involving the Ordinary Least Square (OLS) regression within the framework of E-view 9.0. The study demonstrates that corporate tax avoidance positively impacts shareholders returns in quoted non-financial firms in Nigeria and the effect is improved with better monitoring mechanism in place. We also observe improvement in the liquidity, profitability, expected growth and tangibility of the sampled firms when tax avoidance behavior are well monitored. We recommend among other things that shareholders put in place a monitor mechanism to check management in the use of tax savings to ensure it is in shareholders’ interest.